IPTEKS PENGENDALIAN INTERN ATAS PENERIMAAN NEGARA BUKAN PAJAK (PNBP) PADA KANTOR PELAYANAN SURAT KETERANGAN CATATAN KEPOLISIAN (SKCK) POLDA SULUT - Karo, Lusinda Natalya Debora; Datu, Christian (Universitas Sam Ratulangi, 2018)
The State Budget (APBN) is one thing that is very important for a country because it is a breath for the government in terms of advancing the country. No exception in Indonesia, which is an archipelago with so many regions. The state budget is set every year and carried out for the greatest prosperity of the people. One element of the state budget is the state revenue and grant budget, which is obtained from non-tax state revenues (PNBP). PNBP is a state financial scope that is managed and accounted for so that the Supreme Audit Agency (BPK) as a free and independent audit institution also conducts checks on components that affect state revenues and constitutes state revenues in accordance with the law. PNBP is collected or billed by Government Agencies with an Act or PP order or appointment from the Minister of Finance, based on the PNBP Plan made by the Government Agency Official. One source of Non-Tax State Revenues (PNBP) is obtained in the making of Police Note Certificates (SKCK) that are available throughout the Police of the Republic of Indonesia.Keywords : APBN, PNBP, SKCK,Â Internal Control